7
$\begingroup$

For $x,y,z>0,$ I have to prove that $$ \frac {3 x y z}{(x+y) (y+z) (z+x)} + \sum\limits_{cycl}^{} \left(\frac {x+y}{x+y+ 2 z}\right)^2 \ge \frac {9}{8}.$$

I tried to use $$ \sqrt {\frac {1}{3} \sum\limits_{cycl}^{} (\frac {x+y}{x+y+ 2 z})^2} \ge \frac {1}{3} \sum\limits_{cycl}^{} \frac {x+y}{x+y+ 2 z} \ge \sqrt[3] {(\frac {x+y}{x+y+ 2 z}) (\frac {y+z}{2 x +y +z}) (\frac {z + x}{z+2 y+z})},$$

but it looks hard to continue and $ \frac {3 x y z}{(x+y) (y+z) (z+x)}$ seems to be not helpful. Any help? Thank you.

$\endgroup$
  • $\begingroup$ If you do not get an answer, I would strongly suggest posting to AOPS. Specifically, post in High School Olympiads. $\endgroup$ – greenturtle3141 Jul 18 '18 at 22:04
  • $\begingroup$ it is not possible to solve it in AOPS, in High School Olympiads. Many of the questions are unanswered there $\endgroup$ – Steven Jul 18 '18 at 22:10
  • $\begingroup$ I beg to differ. Many problems there get an answer. People trained in solving these types of math competition problems are quite often found in HSO. $\endgroup$ – greenturtle3141 Jul 18 '18 at 22:15
  • $\begingroup$ is there any solution? $\endgroup$ – Steven Jul 19 '18 at 12:53
5
$\begingroup$

Let $\frac{2x}{y+z}=a$, $\frac{2y}{x+z}=b$ and $\frac{2z}{x+y}=c$.

Thus, $ab+ac+bc+abc=4$ and we need to prove that $$\sum_{cyc}\frac{1}{(a+1)^2}+\frac{3}{8}abc\geq\frac{9}{8}.$$ Now, let $a+b+c=3u$, $ab+ac+bc=3v^2,$ where $v>0$ and $abc=w^3$.

Hence, the condition does not depend on $u$.

In another hand, by AM-GM $$4=ab+ac+bc+w^3=3v^2+w^3\leq3v^2+v^3,$$ which gives $v\geq1$ and since $u\geq v$, we obtain $u\geq1$.

Also, $$4=3v^2+w^3\geq3w^2+w^3,$$ which gives $w\leq1$.

Now, we need to prove that $$\frac{\sum\limits_{cyc}(ab+a+b+1)^2}{(abc+ab+ac+bc+a+b+c+1)^2}+\frac{3}{8}w^3\geq0$$ or $$\frac{\sum\limits_{cyc}(a^2b^2+2a^2+1+2a^2b+2a^2c+4ab+4a)}{(w^3+3v^2+3u+1)^2}+\frac{3}{8}w^3\geq\frac{9}{8}$$ or $$\frac{9v^4-6uw^3+18u^2-12v^2+3+18uv^2-6w^3+12v^2+12u}{(w^3+3v^2+3u+1)^2}+\frac{3}{8}w^3\geq\frac{9}{8}$$ or $f(u)\geq0,$ where $$f(u)=\frac{3v^4-2uw^3+6u^2+1+6uv^2-2w^3+4u}{(w^3+3v^2+3u+1)^2}+\frac{1}{8}w^3-\frac{3}{8}.$$ But $$f'(u)=\tfrac{-2w^3+12u+6v^2+4}{(w^3+3v^2+3u+1)^2}-\tfrac{2\cdot3(3v^4-2uw^3+6u^2+1+6uv^2-2w^3+4u)}{(w^3+3v^2+3u+1)^3}=$$ $$=\frac{2(9uw^3+9uv^2+9v^2+7w^3-w^6-1)}{(w^3+3v^2+3u+1)^3}>0,$$ which says that $f$ increases and since the condition does not depend on $u$, it's enough to prove our inequality for a minimal value of $u$, which happens for an equality case of two variables.

Let $b=a$.

Hence, the condition gives $$a^2+2ac+a^2c=4$$ or $$ac(2+a)=4-a^2$$ or $$c=\frac{2-a}{a},$$ where $0<a<2$ and we need to prove that $$\frac{2}{(a+1)^2}+\frac{1}{\left(\frac{2-a}{a}+1\right)^2}+\frac{3}{8}a^2\cdot\frac{2-a}{a}\geq\frac{9}{8}$$ or $$(a-1)^2(7+2a-a^2)\geq0,$$ which is obvious.

Done!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.